Workshop Pengolahan Data Nilai Siswa Menggunakan Microsoft Excel di SD Negeri Jumeneng - Anita Fira Waluyo; Irma Handayani; Ikrima Alfi; Wahyu Sri Utami; Farida Ardiani; Selfi Artika (Universitas Teknologi Yogyakarta, 2024)
Workshop on processing student grades data using Microsoft Excel is a training activity that aims to introduce the use of Microsoft Excel in managing and analyzing student grades data effectively. This workshop is aimed at teachers at SD Negeri Jumeneng with the aim of increasing their understanding of using Excel as a tool for processing data. In this workshop, the participants will be given an explanation regarding the use of Excel in processing student grade data. The material includes an introduction to relevant basic Excel formulas such as SUM, AVERAGE, MAX, MIN, IF, and others. In addition, participants will also be given guidance on graphing student grade data using Excel. This workshop was carried out through a practical approach by providing training to participants to apply Excel formulas and functions in processing student value data. It is hoped that this workshop will provide significant benefits for teachers at SD Negeri Jumeneng in managing and analyzing student grade data more efficiently using Microsoft Excel.